2018
DOI: 10.1002/aic.16479
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐assisted ammonia decomposition over Fe–Ni alloy catalysts for COx‐Free hydrogen

Abstract: On‐site ammonia (NH3) decomposition is considered as a potential path to supply CO x‐free hydrogen for fuel cell vehicles. In this article, monometallic catalysts (Fe, Co, Ni, and Mo) and bimetallic catalysts (Fe–Co, Mo–Co, Fe–Ni, and Mo–Ni) were prepared and tested in plasma‐catalytic NH3 decomposition, where 6Fe–4Ni catalyst exhibited the highest activity and synergistic capability with plasma. At 500°C, NH3 were completely decomposed (>99.9% NH3 conversion); the rate of H2 production and the energy consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 52 publications
(64 reference statements)
0
62
0
Order By: Relevance
“…31 Similarly, the manner by which the visible light absorber is attached to the metal center is also critical, as a rhenium bipyridine complex in which a BODIPY light absorber is tethered to a Re(bpy)(CO) 3 Cl core via an alkyne linker shows Φ Δ = 0.88. 59 Accordingly molecular topology is an important consideration in the construction of new complexes that support triplet photochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…31 Similarly, the manner by which the visible light absorber is attached to the metal center is also critical, as a rhenium bipyridine complex in which a BODIPY light absorber is tethered to a Re(bpy)(CO) 3 Cl core via an alkyne linker shows Φ Δ = 0.88. 59 Accordingly molecular topology is an important consideration in the construction of new complexes that support triplet photochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized Co 0.89 Fe 2.11 O 4 @mSiO 2 pre-catalyst attained 88% conversion of NH 3 at 600°C and a space velocity of 60 000 cm 3 g −1 h −1 , even maintained for 48 h without attenuation. Similarly, Ni-Fe/Al 2 O 3 , 335,336 Ni-Fe alloys 337 and NiCo/Ce 0.6 Zr 0.3 Y 0.1 O 2 solid solutions 338 were found to show higher catalytic performance than the single metal pre-catalyst toward the decomposition of NH 3 .…”
Section: Bimetallic Catalystsmentioning
confidence: 93%
“…Bimetallic catalysts with unique structures may achieve excellent catalytic activity in comparison with their individual monometallic components. To date, a series of bimetallic catalysts, such as Co-Mo, [327][328][329] Fe-Mo, 330 Fe-Co, [331][332][333][334] Fe-Ni [335][336][337] and Co-Ni, 338 have been prepared and employed as catalysts for NH 3 decomposition. For example, Duan et al reported that the bimetallic Co-Mo/MCM-41 pre-catalyst shows a higher activity in the NH 3 decomposition reaction than a monometallic Co/MCM-41 or Mo/MCM-41 pre-catalyst under the same conditions.…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
“…Next to Ru-catalysts, other supported metal catalysts were tested for plasma-catalytic ammonia synthesis (and ammonia decomposition). 131,152,156,157,159,168,276,277,279,280,[287][288][289][290][291][292] In most cases, supported Co, Ni, and Rh catalysts are found to be most active among the tested catalysts. 131,156,159,276,277 Such metals have less ammonia desorption limitations than the classical Fe and Ru catalysts for thermal-catalytic ammonia synthesis.…”
Section: Performance In Various Types Of Plasma Reactorsmentioning
confidence: 98%